Network pharmacology-based study on immunomodulatory mechanism of danggui-yimucao herb pair for the treatment of RU486-induced abortion. (10th January 2022) - Bi, Shi-Jie; Huang, Yu-Xi; Feng, Li-Mei; Yue, Shi-Jun; Chen, Yan-Yan; Fu, Rui-Jia; Xu, Ding-Qiao; Tang, Yu-Ping
Abstract: Ethnopharmacological relevance: The Danggui-Yimucao herb pair (DY) is a classic combination in Chinese herbal formulas, consisting of the root of Angelica sinensis (Oliv.) Diels and the aerial parts of Leonurus japonicus Houtt. DY first appeared in "Zhulinsi fuke mifang" in the Jin Dynasty, and it has a long history as a drug for the treatment of abortion. However, its underlying immunomodulatory mechanisms involved are still unclear. Aim of the study: In this study, network pharmacology and pharmacological experiments were used to explore the role and mechanism of DY in the treatment of medical abortion. Materials and methods: Network pharmacology was used to establish the relationship between the components of DY and abortion-related targets, and to enrich important pathways and biological process for verification. ELISA was used to assess progesterone levels. Flow cytometry was used to detect the degree of differentiation of Th1/Th2 cells. Immunohistochemical methods and qPCR were used to measure the expression levels of T-bet, GATA-3 and IL-4. Results: Through the prediction analysis of network pharmacology, we found that key pathway for DY treatment of abortion, such as anemia, pelvic infection, immune disorders, and coagulation disorders, was Th1/Th2 cell differentiation pathway. The pharmacological results revealed that DY greatly corrected the imbalance of Th cell subsets in abortion mice, significantly inhibited the differentiation of Th2 cells, and resulted in an increase in the Th1/Th2 ratio. In addition, the concentration of progesterone in the serum of mice after abortion was significantly reduced. We also found that DY upregulated spleen T-bet and downregulated IL-4 gene expression in mice. Besides, immunohistochemical results showed that DYE could up-regulate T-bet but inhibit GATA-3 expression. Conclusions: Our results showed that after RU486-induced abortion, progesterone and Th1/Th2 paradigm were disordered in mice, but DY could make mice recover more quickly, which indicated that DY had great development value in immunoregulation. Graphical abstract: Image 1